НАТО В СИСТЕМЕ МЕЖДУНАРОДНЫХ ОРГАНИЗАЦИЙ (Journal of actual problems of jurisprudence, 2019)
In the given article the author considers of the new purposes and directions in activity of the NATO for maintenance of theinternational safety.